Hybridization biosensor based on the covalent immobilization of probe DNA on chitosan–mutiwalled carbon nanotubes nanocomposite by using glutaraldehyde as an arm linker - Wang, Qingxiang; Zhang, Bin; Lin, Xiaoqiang; Weng, Wen (Sensors and actuators. B, Chemical, 2011)
A label-free DNA biosensor for hybridization detection of short DNA species related to the transgenic plants gene fragment of cauliflower mosaic virus (CaMV) 35S promoter was developed in this paper. The nanocomposite containing chitosan (CS) and mutiwalled carbon nanotubes (MWNTs) was first coated on a glassy carbon electrode. Then a highly reactive dialdehyde reagent of glutaraldehyde (GTD) was applied as an arm linker to covalently graft the 5′-amino modified probe DNA to the CS–MWNTs surface via the facile aldehyde–ammonia condensation reaction. The hybridization capacity of the developed biosensor was monitored with electrochemical impedance spectroscopy (EIS) using [Fe(CN) 6] 3−/4− as an indicating probe, and the experimental results showed that the biosensor had fast hybridization rate and low background interference. A wide dynamic detection range (1.0 × 10 −13–5 × 10 −10 M) and a low detection limit (8.5 × 10 −14 M) were achieved for the complementary sequence. In addition, the hybridization specificity experiments showed that the sensing system can accurately discriminate complementary sequence from mismatch and noncomplementary sequences.